Analyze the Potential of the Wood Processing Industry to Export to the European Union Market: A Case Study of the Wood Processing Industry in Bolikhamxay Province: https://doi.org/10.69692/SUJMRD1004132 - phommalin, soukan; phonetip, khamtan; chanthavong, Bakham (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to analyze the challenges associated with exporting wood products to the European market and evaluate the production readiness of the wood processing industry. The study employs SWOT analysis, the Ishikawa diagram, and FMEA to assess the strengths and weaknesses to identify the root causes of problems, and propose potential solutions for wood processing factories in Bolikamxay Province. Data has been collected from relevant sectors, including the Department of Agriculture and Forestry, the Department of Industry and Trade, and the Department of Finance in Bolikamxay Province. The results of the study also found that the wood processing industries in Bolikhamxay Province (9 factories) are equipped with machinery and labor at a moderate level with an average value equal to 2.97 and 3.17 respectively, in this only 1 factory has more machine equipment than the others at a very good level with an average value equal to 4.55 because the factory has all the machines along the production line and is a factory managed by foreigners. There are only 3 factories with a good level of labor competency at the average of 3.83 because these 3 factories have foreign workers such as Vietnamese and Indian at good labor skills. The study concluded that Bolikhamxay Province currently does not export wood products to Europe; however, exports to neighboring countries, including Thailand, Vietnam, and China. Laos and European regulations related to 13 specific criteria for exporting wood products. As the case of Bolikhamxay Province can meet only 3 criteria, which equates to 7.69% compliance. This indicates that 92.31% of the criteria remain unmet. This study found that in order to be ready to export wood products to the European market, wood processing industry operators in Bolikhamxay province must improve their machinery and labor skills.